Population pharmacokinetics of oseltamivir and oseltamivir carboxylate in obese and non‐obese volunteers. (4th March 2016) - Chairat, Kalayanee; Jittamala, Podjanee; Hanpithakpong, Warunee; Day, Nicholas P. J.; White, Nicholas J.; Pukrittayakamee, Sasithon; Tarning, Joel
Abstract : Aims: The aims of the present study were to compare the pharmacokinetics of oseltamivir and its active antiviral metabolite oseltamivir carboxylate in obese and non‐obese individuals and to determine the effect of obesity on the pharmacokinetic properties of oseltamivir and oseltamivir carboxylate. Methods: The population pharmacokinetic properties of oseltamivir and oseltamivir carboxylate were evaluated in 12 obese [body mass index (BMI) ≥30 kg m −2 ) and 12 non‐obese (BMI <30 kg m −2 ) Thai adult volunteers receiving a standard dose of 75 mg and a double dose of 150 mg in a randomized sequence. Concentration–time data were collected and analysed using nonlinear mixed‐effects modelling. Results: The pharmacokinetics of oseltamivir and oseltamivir carboxylate were described simultaneously by first‐order absorption, with a one‐compartment disposition model for oseltamivir, followed by a metabolism compartment and a one‐compartment disposition model for oseltamivir carboxylate. Creatinine clearance was a significant predictor of oseltamivir carboxylate clearance {3.84% increase for each 10 ml min −1 increase in creatinine clearance [95% confidence interval (CI) 0.178%, 8.02%]}. Obese individuals had an approximately 25% (95% CI 24%, 28%) higher oseltamivir clearance, 20% higher oseltamivir volume of distribution (95% CI 19%, 23%) and 10% higher oseltamivir carboxylate clearance (95% CI 9%, 11%) compared with non‐obese individuals. However, these altered pharmacokinetic properties were small and did not change the overall exposure to oseltamivir carboxylate. Conclusions: The results confirmed that a dose adjustment for oseltamivir in obese individuals is not necessary on the basis of its pharmacokinetics.